The Grand Paloma Resort : a novel - Natera, Cleyvis (Ballantine Books, 2025)
"The Grand Paloma Resort is a lush paradise in the Dominican Republic where the guests enjoy incredible luxury, and the staff is always eager to please-that is, until they are pushed to the brink"-- Provided by publisher.